Coping (Enfrentamento) religioso-espiritual em pacientes com hepatite C durante a terapêutica medicamentosa - Reis, Manuela Ribeiro dos (2012)
Hepatitis C is an infectious disease caused by virus HCV and that affects, especially the liver, and is generally asymptomatic. Most of the times, many are unaware of the true way of contamination of the disease. Hepatitis C is considered a major public health problem in Brazil and in the world, in front of the number of people infected by the virus. The medications used in the treatment of hepatitis C can cause many adverse effects in the course of drug therapy, compromising the quality of life affecting your well-being. Faced with this reality, the purpose of this research was to verify the expression of Coping Religious Spiritual in 30 patients with hepatitis C during the drug. The reference population reference constitutes of 30 patients with hepatitis C, assisted by the clinic of the House of Hepatitis from the Federal University of São Paulo in the first three months of treatment, with age over 18 years. The instruments used in collection of data were: General Questionnaire (Demographic data, socio-economic, religious and health) and Scale Coping Religious Spiritual. Many of these patients showed the connection between religion and/or spirituality, health and well-being, as well as answers resilient with Coping. We are living through a time where science and religions are united, and seals have fueled the patient find strength and benevolence in face of crises